2021
DOI: 10.1002/jmv.26953
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 models of frequently contacted animals provide clues of their SARS‐CoV‐2 S protein affinity and viral susceptibility

Abstract: The outbreak of atypical pneumonia (coronavirus disease 2019 ) has been a global pandemic and has caused severe losses to the global economy. The virus responsible for COVID-9, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), has a spike glycoprotein (S protein) that binds angiotensin-converting enzyme 2 (ACE2) present on host cell membranes to gain entry. Based on the full-length human ACE2 cryo-EM structure, we generated homology models of full-length ACE2 proteins from various species (gorilla,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
0
14
0
1
Order By: Relevance
“…Additionally, the clinical respiratory tract infections show similarities [30]. Because of all these resemblances, BCoV has already been suggested and successfully employed as a SARS-CoV(-2) surrogate in many different applications [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the clinical respiratory tract infections show similarities [30]. Because of all these resemblances, BCoV has already been suggested and successfully employed as a SARS-CoV(-2) surrogate in many different applications [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…There are several other species, for example, cats, dogs, or minks, that are also susceptible to SARS-CoV-2, but they have differences in the ACE2 receptors sequences. Moreover, the previous studies revealed evidence that the human ACE2 receptor has the highest binding affinity to SARS-CoV-2 compared to other animal species [ 14 16 ]. Those differences should be taken into consideration during animal SARS-CoV-2 infection studies.…”
Section: Animal Models For Sars-cov-2mentioning
confidence: 99%
“…SARS-CoV-2 foi detectado em cães domésticos (Canis familiaris) em diversos estudos, porém esses animais apresentam-se assintomáticos ou com sinais e sintomas leves durante a infecção (Sit et al, 2020;Hamer et al, 2022;Barroso-Arévalo et al, 2022;Jairak et al, 2022;Medkour et al, 2022;Rivero et al, 2022;Zambrano-Mila et al, 2022). Embora a afinidade do receptor ACE2 de cães para o SARS-CoV-2 seja considerada alta (Wu et al, 2020;Koley et al, 2021;Ma & Gong, 2021;Zhang et al, 2021), esse fator não é o único preditor de susceptibilidade ao vírus (Wu et al, 2020;Koley et al, 2021;Ma & Gong, 2021;Piplani et al, 2021). Patterson et al (2020) examinaram 919 cães domésticos na Itália no auge da pandemia nesse país, encontrando anticorpos contra o SARS-CoV-2 em 3,3% desses animais, porém nenhum cão foi positivo ao exame de PCR para a detecção de partículas virais.…”
Section: O Vison Europeu (Mustela Vison) E O Vison Americano (Neoviso...unclassified